Teori Kepribadian Behavioristik - Dwi Octaria; Yusi Riksa Yustiana (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This article reviews the development of personality theories within the behavioral framework and their expansion into the social cognitive approach, based on a review of Yustinus Semiun's book "Behavioristic Personality Theories." This review aims to map the evolution of behavioral thought from its foundational emphasis on environmental determinism toward the recognition of the role of cognitive and social processes in personality formation. Through a library research approach, this article analyzes three main perspectives of behaviorism: Ivan Pavlov's classical conditioning, Edward Thorndike's law of effect, and B.F. Skinner's operant conditioning, as well as their further development in Albert Bandura’s and Walter Mischel’s social cognitive theories. The analysis shows that although classical behavioral theories provide a systematic framework for understanding behavior through stimulus-response associations and environmental consequences, these theories face limitations in explaining cognitive complexity, intrinsic motivation, and human social dynamics. Social cognitive theory emerges as a correction and refinement by incorporating observational elements, self-regulation, and individuals' cognitive interpretations of social contexts. The conclusion affirms that integrating behavioral and social cognitive principles offers a more holistic understanding of personality as the result of dynamic interactions between environment, behavior, and cognitive processes, with significant implications for education, therapy, and psychosocial intervention. Keywords: behaviorism, social cognitive, personality, learning, classical conditioning, operant conditioning, self-regulation.   Abstrak Artikel ini mengulas perkembangan teori-teori kepribadian dalam kerangka behavioristik dan perluasannya ke dalam pendekatan kognitif sosial, berdasarkan tinjauan terhadap buku “Teori-teori Kepribadian Behavioristik” karya Yustinus Semiun. Ulasan ini bertujuan untuk memetakan evolusi pemikiran behavioristik dari fondasi awal yang menekankan determinisme lingkungan menuju pengakuan atas peran proses kognitif dan sosial dalam pembentukan kepribadian. Melalui pendekatan studi kepustakaan, artikel ini menganalisis tiga perspektif utama behaviorisme: classical conditioning Ivan Pavlov, hukum efek Edward Thorndike, dan operant conditioning B.F. Skinner, serta perkembangan lanjutannya dalam teori kognitif sosial Albert Bandura dan Walter Mischel. Hasil analisis menunjukkan bahwa meskipun teori behavioristik klasik memberikan kerangka sistematis untuk memahami perilaku melalui asosiasi stimulus-respons dan konsekuensi lingkungan, teori-teori ini menghadapi keterbatasan dalam menjelaskan kompleksitas kognitif, motivasi intrinsik, dan dinamika sosial manusia. Teori kognitif sosial muncul sebagai koreksi dan penyempurnaan dengan memasukkan elemen observasional, regulasi diri, dan interpretasi kognitif individu terhadap konteks sosial. Simpulan artikel ini menegaskan bahwa integrasi antara prinsip behavioristik dan kognitif sosial menawarkan pemahaman yang lebih holistik tentang kepribadian sebagai hasil dari interaksi dinamis antara lingkungan, perilaku, dan proses kognitif, serta memiliki implikasi signifikan bagi pendidikan, terapi, dan intervensi psikososial. Kata kunci: behaviorisme, kognitif sosial, kepribadian, pembelajaran, classical conditioning, operant conditioning, regulasi diri.